2020
DOI: 10.3390/nu12071979
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Healthy Eating in Spanish High Schools

Abstract: Obesity and overweight are both public health problems, affecting increasingly younger populations. Promoting healthy eating should be a must in schools. Therefore, getting to know the eating habits of a population group as sensitive as adolescents and whether their schools apply an appropriate policy for their nutrition should be a priority. Therefore, the objective of this study was to discover whether the Secondary Education High Schools of Huelva and its province could be considered as centres that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…It is essential to determine who is more likely to miss breakfast and the causes of this behaviour [ 17 ]. According to prior research, kids with lower social and economic positions, less-educated parents, and parents who have divorced are more likely than other students to miss breakfast [ 16 , 18 ]. Investigations revealed that students' lack of time in the morning, diminished appetite, and worries about their weight and appearance were the top causes of breakfast skipping [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to determine who is more likely to miss breakfast and the causes of this behaviour [ 17 ]. According to prior research, kids with lower social and economic positions, less-educated parents, and parents who have divorced are more likely than other students to miss breakfast [ 16 , 18 ]. Investigations revealed that students' lack of time in the morning, diminished appetite, and worries about their weight and appearance were the top causes of breakfast skipping [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition is one of the most relevant aspects of childhood and adolescent care due to its consequences on the overall development of the person [ 4 , 5 ]. Knowing the eating habits of adolescents and finding out whether secondary schools apply an adequate policy should be a priority [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that content on healthy eating in secondary school curricula is scarce, and if it exists at all, it plays a negligible part in the curriculum [ 6 , 9 , 10 , 11 , 12 , 13 , 14 ]. In addition to few practical activities in schools, different degrees of non-compliance or ignorance of regulations on this issue have also been identified [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations